Improvement of antioxidant activity and active ingredient of Dendrobium officinale via microbial fermentation - Yu, Gen; Xie, QingFen; Su, WenFeng; Dai, Shuang; Deng, XinYi; Gu, QuLiang; Liu, Shan; Yun, JeonYun; Xiang, WenHao; Xiong, Yang; Yang, GuanDong; Ren, Yifei; et al. (Frontiers in Microbiology, 2023)
This study used brewer's yeast to ferment Dendrobium officinale. and single-factor and orthogonal experiments were conducted to determine the optimal fermentation conditions. The antioxidant capacity of Dendrobium fermentation solution was also investigated by in vitro experiments, which showed that different concentrations of fermentation solution could effectively enhance the total antioxidant capacity of cells. The fermentation liquid was found to contain seven sugar compounds including glucose, galactose, rhamnose, arabinose and xylose using gas chromatography-mass spectrometry (GC-MS) and ultraperformance liquid chromatography-quadrupole-time of flight mass spectrometry (HPLC-Q-TOF-MS), with the highest concentrations of glucose and galactose at 194.628 μg/mL and 103.899 μg/mL, respectively. The external fermentation liquid also contained six flavonoids with apigenin glycosides as the main structure and four phenolic acids including gallic acid, protocatechuic acid, catechol and sessile pentosidine B.